The Effects of Maltreatment and Family Structure on Minor and Serious Delinquency - Heck, Cary (International journal of offender therapy and comparative criminology, 2000)
This study explores the influence of maltreatment on serious violent and property delinquency as well as on minor misbehavior offenses among a sample of White male delinquents. A recent influential study concluded that this relationship has been exaggerated and found it to be nonexistent for serious offending after the effects of family structure were factored in. This article points out some of the deficiencies in that research and demonstrates that when both delinquency and maltreatment are measured comprehensively, the relationship is robust controlling for type of family structure, verbal IQ, family size, and birth order. Although it was found that the variables impact differentially according to the type of delinquency being examined, in every case, maltreatment was found to account for significant independent variance. It was also found that delinquents from homes broken by desertion were the most maltreated and the most delinquent